Hoosiers on the Home Front - Bakken, Dawn E. (Book collections on Project MUSE., 2022)
"Wars are fought on the home front as well as the battlefront. Spouses, family, friends, and communities are called upon to sacrifice and persevere in the face of a changed reality. Hoosiers on the Home Front explores the lives and experiences of ordinary Hoosiers from around Indiana who were left to fight at home during wartimes. Drawn from the rich holdings of the Indiana Magazine of History, a journal of state and midwestern history published since 1905, this collection includes original diaries, letters and memoirs, and research essays-all focused on Hoosiers on the home front of the Civil War through the Vietnam War. Readers will meet, among others, Joshua Jones of the 19th Indiana Volunteer Regiment and his wife, Celia; Attia Porter, a young resident of Corydon, Indiana, writing to her cousin about Morgan's Raid; Civil War and World War I veterans who came into conflict over the Indianapolis 500 and Memorial Day observances; Virginia Mayberry, a wife and mother on the World War II home front; and university students and professors-including antiwar activist Howard Zinn and conservative writer R. Emmett Tyrrell Jr.-clashing over the Vietnam War. Hoosiers on the Home Front offers a compelling glimpse of how war impacts everyone, even those who never saw the front line"--